As(III) and As(V) removal mechanisms by Fe-modified biochar characterized using synchrotron-based X-ray absorption spectroscopy and confocal micro-X-ray fluorescence imaging. (May 2020) - Xu, Yong; Xie, Xianjun; Feng, Yu; Ashraf, Muhammad Aqeel; Liu, YingYing; Su, Chunli; Qian, Kun; Liu, Peng
Graphical abstract: Highlights: As(III/V) removal by Fe-modified biochars depended on pyrolysis temperature. As diffused deeper into particle as pyrolysis temperature increased. The oxidation from As(III) to As(V) was enhanced as pyrolysis temperature increased. The addition of calcite promoted As removal and As(III) oxidation. Abstract: Batch experiments followed by solid-phase analyses were conducted to explore As(III) and As(V) removal mechanisms by Fe-modified biochars (FeBC) pyrolyzed at different temperatures (300, 600, and 900 °C). Arsenic removal by FeBC, best described by pseudo-second order kinetic and Langmuir isotherm models, increased from 73.8 to 99.9% for As(III) and 86.8 to 99.9% for As(V) as the pyrolysis temperature increased. The addition of calcite enhanced the removal efficiency (all > 99%). Confocal micro-X-ray fluorescence imaging (CMXRFI) analyses indicated As co-located with Fe and diffused deeper into the particles as the pyrolysis temperature increased. For As(III)-spiked systems, X-ray absorption near-edge structure (XANES) data indicated 20.2 to 81.5% of As(III) was oxidized to As(V) as the pyrolysis temperature increased; an increase of oxidation efficiency was observed after adding calcite. For As(V)-spiked systems, no As(V) reduction was observed. Overall, As(III/V) removal using FeBC was affected by the spatial distribution and species of As.